The relationship between the persistent illusion of movement and traumatic anxiety in a non-clinical sample - Dellar, Brendon (Curtin University, 2006)
This thesis was concerned with investigating a visual-illusionary phenomenon that co-occurs with post-traumatic anxiety symptoms. More specifically, individuals who report recurring specific memories of a fearful event (RSM) also tend to report a persistent illusion of movement (PIM) upon prolonged visual fixation (Tym, Dyck & McGrath, 2000). The development of a visual test (i-Test) designed to reliably elicit PIM has enabled research to be conducted on the nature and correlates of this type of visual disturbance. The present research aimed: 1) To develop a standard protocol for assessment of PIM and RSM; 2) to test the reliability of the i-Test in eliciting PIM in a student sample 3) to test the predictive relationship between dissociation and anxiety symptoms with PIM and RSM 4) to formulate and test a hypothesis regarding a mechanism underlying PIM. The first study screened 142 participants for RSM and PIM using self-administered questionnaires designed by Tym (personal communication, 2001). There was an unexpectedly high rate (54.2%) of PIM and RSM (37.3%) in the sample, which appeared to be the product of questionnaire design limitations. Two semi-structured interviews were developed and subsequently tested on a new sample of 50 participants in Study 2. Study 2 documented intra-rater and inter-rater reliability co-efficient of sufficient strength to indicate good reliability for the semi-structured interviews. The results of Study 2 indicate that PIM is a relatively stable symptom over a 30-minute and one-week test-retest time frame.The onset time for PIM was relatively consistent between participants, with a mean latency of approximately 7 seconds. The oscillation rate of PIM was relatively consistent between individuals, with a mean average oscillation of approximately 0.8Hz. The third study tested a sample of 148 participants using the revised assessment protocols. The base rate for PIM (16.2%) and RSM (18.9%), and the concordance rates (46% to 54%) were slightly stronger than the Tym et al. (2000) community based study (33%). In addition to this, 11 other illusionary phenomena were documented, however none of these visual symptoms significantly correlated with RSM. The average oscillation rate is comparable to the rate documented in Study 2, further establishing the consistency of the reported rate of PIM oscillations between individuals. In Study 3, each participant was assessed for levels of dissociation (Dissociative Experiences Scale), somatic arousal (Mood and Anxiety Symptoms Questionnaire – Anxious Arousal Scale) and anxiety sensitivity (Anxiety Sensitivity Index). The results indicate that gender and dissociation significantly predict RSM status, and self-reported levels of anxious-arousal significantly predict PIM status. A multiway frequency analysis between the sub-components of RSM and PIM revealed that the physiological arousal inducing properties of the recurring memory is the only significant predictor of PIM.The observed relationship between RSM and PIM may reflect the broader relationship between anxiety and dissociation. A pulsatile hypothesis was proposed as a feasible mechanism underlying PIM, due to the rhythmical nature of the visual disturbance, the range of the documented oscillations, and its specificity to psychological disorders characterised by cardiovascular sensitivities. All participants were administered the i-Test prior to and following aerobic exercise aimed at increasing pulse rate to 80% of maximum load. An increase in physical exertion significantly increased the latency of PIM onset, but did not impact on the rate of PIM. PIM rate appeared relatively consistent between individuals at 0.6Hz to 0.8Hz at the pre-exercise condition. Several participants who reported PIM also displayed obvious nystagmoid-like movements during the i-Test perceptual task. The role of eye-movements in PIM requires further investigation by future ophthalmological research. The final aim of Study 3 was to investigate the relationship between RSM/PIM and flicker sensitivity. Through the use of a Critical Flicker Frequency/Fusion task (CFF), each participant’s sensitivity to flicker was determined. In addition to detecting sensitivity thresholds, CFF is also considered to be a reliable indicator of the level of cortical arousal.The results of this study suggest that individuals with RSM have a higher sensitivity to flicker than other participants, however there was a non-significant relationship between CFF and PIM. The lack of relationship between PIM and CFF may be due to issues concerning statistical power and effect-size. Future research is required to investigate this link in more detail. The overall results of this thesis suggest that i-Test elicited PIM is a reliable phenomenon that is associated with higher rates of traumatic memories when compared with persons who do not report this visual symptom. The strength of the association between RSM and PIM, however, does not support the use of the i-Test as a marker for the presence of RSM outside a clinical sample. The reliability of PIM as a phenomenon and its association with anxiety symptoms may be of theoretical importance in enabling future research to investigate the relationship between visual symptoms and anxiety-related pathology.